2003
DOI: 10.1051/0004-6361:20030095
|View full text |Cite
|
Sign up to set email alerts
|

The soft X-ray characteristics of solar flares, both with and without associated CMEs

Abstract: The complex relationship between solar flares and coronal mass ejections is investigated using a comparison of flare parameters for a total of 69 ejective and non-ejective flares. In the case of solar flares which do not show mass ejection there seems to be a clear relationship between the peak intensity and duration, with higher intensity events being of longer duration. Systematic differences in the relationship between peak temperature and intensity for the two types of event are also evident, with flares a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
24
1
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 27 publications
9
24
1
1
Order By: Relevance
“…figure 3) in accordance with previous results in [5] and [7] although the latter derive these results comparing duration to peak intensity. As regards Flare rise time versus decay time no systematic difference appears for the two subgroups in accordance with similar results in [7].…”
supporting
confidence: 93%
“…figure 3) in accordance with previous results in [5] and [7] although the latter derive these results comparing duration to peak intensity. As regards Flare rise time versus decay time no systematic difference appears for the two subgroups in accordance with similar results in [7].…”
supporting
confidence: 93%
“…This model supports the proposal by Delannée & Aulanier (1999) that EIT waves are related to the magnetic restructuring in CMEs. The results of Kay et al (2003) also favor the idea that a CME is a necessary condition for the appearance of EIT waves during flares, although most of the non-CME flares in their sample have peak intensities below the M class.…”
Section: Discussionmentioning
confidence: 53%
“…Regarding the second question, Biesecker et al (2002) found an unambiguous correlation between EIT waves and CMEs, and a significantly weaker correlation of EIT waves with flares. Kay et al (2003) also found that all "EIT wave"-associated flares are accompanied by CMEs. Recently, Cliver et al (2005) pointed out that about half of the EIT waves observed from 1997 March to 1998 June were associated with small solar flares below the C class, which implies that it is unlikely that it is the pressure pulse in the flare that causes a fast-mode wave to be observed as EIT waves.…”
Section: Introductionmentioning
confidence: 83%
“…Therefore, "EIT waves" are EIT waves 57 a phenomenon intrinsically connected with CMEs. The speeds of these "EIT waves"-associated CMEs range from ∼200-1800 km s −1 , and there is no correlation between the occurrence of an "EIT wave" and the linearly fitted speed of the CME (Kay et al 2003).…”
Section: Introductionmentioning
confidence: 95%